The Making of Our Bodies, Ourselves : How Feminism Travels across Borders - Davis, Kathy, 1949- (Book collections on Project MUSE., 2007)
The story of how the feminist classic Our Bodies, Ourselves has been adapted and reworked by women of different cultures around the world.